Neuroanatomy Learning: Augmented Reality vs. Cross‐Sections. Issue 3 (19th July 2019) - Henssen, Dylan J.H.A.; van den Heuvel, Loes; De Jong, Guido; Vorstenbosch, Marc A.T.M.; van Cappellen van Walsum, Anne‐Marie; Van den Hurk, Marianne M.; Kooloos, Jan G.M.; Bartels, Ronald H.M.A.
Abstract : Neuroanatomy education is a challenging field which could benefit from modern innovations, such as augmented reality (AR) applications. This study investigates the differences on test scores, cognitive load, and motivation after neuroanatomy learning using AR applications or using cross‐sections of the brain. Prior to two practical assignments, a pretest (extended matching questions, double‐choice questions and a test on cross‐sectional anatomy) and a mental rotation test (MRT) were completed. Sex and MRT scores were used to stratify students over the two groups. The two practical assignments were designed to study (1) general brain anatomy and (2) subcortical structures. Subsequently, participants completed a posttest similar to the pretest and a motivational questionnaire. Finally, a focus group interview was conducted to appraise participants' perceptions. Medical and biomedical students ( n = 31); 19 males (61.3%) and 12 females (38.7%), mean age 19.2 ± 1.7 years participated in this experiment. Students who worked with cross‐sections ( n = 16) showed significantly more improvement on test scores than students who worked with GreyMapp‐AR ( P = 0.035) ( n = 15). Further analysis showed that this difference was primarily caused by significant improvement on the cross‐sectional questions. Students in the cross‐section group, moreover, experienced a significantly higher germane ( P = 0.009) and extraneous cognitive load ( P = 0.016) than students in the GreyMapp‐AR group. No significant differences were found in motivational scores. To conclude, this study suggests that AR applications can play a role in future anatomy education as an add‐on educational tool, especially in learning three‐dimensional relations of anatomical structures.